Common Errors Identification in Pronouncing Silent Letters in English Words by EFL Novices - Ali Mohammed Saleh Al-Hamzi; Lilla Musyahda (Master Program in Linguistics, Diponegoro University, 2022)
In English, the sound system is somewhat distinct from Arabic. Yemeni Novices have many difficulties pronouncing English terms owing to this. For example, we often hear English learners pronounce